Europium(III) Concentration Effect on the Spectroscopic and Photoluminescent Properties of BaMoO4:Eu - Rosa, Ieda L. V.; Marques, Ana Paula A.; Tanaka, Marcos T. S.; Motta, Fabiana V.; Varela, José Arana [UNESP]; Leite, Edson R.; Longo, Elson [UNESP] (Springer/plenum Publishers, 2009)
BaMoO4:Eu (BEMO) powders were synthesized by the polymeric precursor method (PPM), heat treated at 800 A degrees C for 2 h in a heating rate of 5 A degrees C/min and characterized by powder X-ray diffraction patterns (XRD), Fourier Transform Infra-Red (FTIR) and Raman spectroscopy, besides room temperature Photoluminescence (PL) measurements. The emission spectra of BEMO samples under excitation of 394 nm present the characteristic Eu3+ transitions. The relative intensities of the Eu3+ emissions increase as the concentration of this ion increases from 0.01 to 0.075 mol, but the luminescence is drastically quenched for the Ba0.855Eu0.145MoO4 sample. The one exponential decay curves of the Eu3+ 5D0 -> F-7(2) transition, lambda (exc) = 394 nm and lambda (em) = 614 nm, provided the decay times of around 0.54 ms for all samples. It was observed a broadening of the Bragg reflections and Raman bands when the Eu+3 concentration increases as a consequence of a more disordered material. The presence of MoO3 and Eu2Mo2O7 as additional phases in the BEMO samples where observed when the Eu3+ concentration was 14.5 mol%.
Keywords: Europium; Molybdate; Complex Polymerization Method; Photoluminescence